2007
DOI: 10.1111/j.1442-2050.2007.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum p53 antibody as a predictor of early recurrence in patients with postoperative esophageal squamous cell carcinoma

Abstract: It is reported that surveillance of serum p53 antibody (Ab) is a useful marker in detecting esophageal squamous cell carcinoma (ESCC). But there is little reported about prognostic significance of serum p53-Ab in postoperative patients with ESCC. The aim of this study is to evaluate the significance of preoperative serum p53-Ab as a marker of early recurrence after curative resection for ESCC. Enzyme-linked immunosorvent assay (ELISA) was used to analyze serum p53-Ab before treatment in 44 patients with ESCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…After completion of treatment, patients were reviewed within 4–6 weeks, then every 3 months in the first 2 years, every 4 months in the third year, and every 6 months thereafter. Physical examinations included serum tumor markers of carcino-embryonic antigen (CEA), squamous cell carcinoma-related antigen (SCC), cytokeratin 19 fragment (CYFRA), and p53 (each month) [ 17 – 20 ]. Other studies performed routinely were upper gastrointestinal endoscopy (+/− biopsy) every 3–4 months, CT scans of the thorax and upper abdomen every 2–3 months, and PET/CT scans every 6–12 months or when a recurrence was suspected by other examinations.…”
Section: Methodsmentioning
confidence: 99%
“…After completion of treatment, patients were reviewed within 4–6 weeks, then every 3 months in the first 2 years, every 4 months in the third year, and every 6 months thereafter. Physical examinations included serum tumor markers of carcino-embryonic antigen (CEA), squamous cell carcinoma-related antigen (SCC), cytokeratin 19 fragment (CYFRA), and p53 (each month) [ 17 – 20 ]. Other studies performed routinely were upper gastrointestinal endoscopy (+/− biopsy) every 3–4 months, CT scans of the thorax and upper abdomen every 2–3 months, and PET/CT scans every 6–12 months or when a recurrence was suspected by other examinations.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the traditional tumor markers, these autoantibodies were shown to be useful molecular markers for ESCC. Some patients with ESCC mount an immunological reaction against several tumor-associated antigens, including p53 [5-7], myomegalin [8] and TRIM21 [9]. Recently, a proteomics-based approach identified several autoantibodies in sera of patients with ESCC, such as anti-heat shock protein 70 [10] and anti-peroxiredoxin VI [11].…”
Section: Introductionmentioning
confidence: 99%
“…As with any retrospective study, this series needs to be confirmed by other retrospective and if possible prospective studies. Table 5 shows the prognostic value of p53 mutations for overall survival [8-10,14-16], event-free survival [9,17] and response rate [8,9,18] in other reports on esophageal cancer. Those values are consistent with the findings reported here.…”
Section: Discussionmentioning
confidence: 99%